Evaluation of interleukin-6 and Tumor Necrosis Factor- Alpha in tears and its associated factors in age-related macular degeneration patients - Rosli, Abdul Hadi (2021)
OBJECTIVE: The objective of this study was to evaluate the Interleukin-6 (IL-6) and Tumor Necrosis Factor-Alpha (TNF-α) in tears in age related macular degeneration (AMD) patients and to determine its associated factors. METHODS: This was a comparative cross-sectional study. Patients with Early AMD, Late AMD and Control group whom fulfilled the inclusion criteria were recruited into this study. Tears samples were collected, then analysed using commercial Human IL-6 and TNF-α enzyme-linked immunosorbent assay kit to measure IL-6 and TNF-α levels in tears. Only late neovascular AMD (nAMD) was enrolled in this study since there was no late dry AMD available during the study period. RESULTS: A total of 142 patients (56 early AMD, 56 late nAMD and 30 Control group) were recruited in this study. AMD showed significantly higher mean tears IL-6 (21.91 (95%CI: 19.89, 23.93), p= 0.014) compared to control group after adjusted with covariates. However there was no significant difference of mean tears IL-6 between early and late nAMD group after adjusted with covariates (p=0.844). For TNF-α, there was no significant differences of mean tears TNF- α between AMD and control group as well as between early and late nAMD after adjusted with covariates (p=0.324 and p=0.749 respectively). There was no significant association found between IL-6 and TNF-α level in tears with duration of AMD, serum level of IL-6 and TNF-α, smoking status and AMD status. CONLUSION: IL-6 in tears showed significant elevation among AMD. Therefore, IL-6 in tears can be used as non-invasive biomarker for AMD screening.